Transcriptional analysis of intestinal colonization by Salmonella enteritidis PT4 in 1-day chickens using microarray - Alfitouri, Abdulgader Dhawi (2012)
The recent association between S. Enteritidis PT4 and poultry products has caused a great deal of concern from adverse publicity and with resulting national and international requirements to control the major food-poisoning Salmonella serotypes at the breeder and layer levels in order to ensure that poultry products are Salmonella-free. The exact mechanism whereby these serotypes are able to colonise the intestine of chickens is still exactly unknown. Indeed, there is increasing evidence that colonisation is not solely a metabolic function but that some form of physical association with cells or an organ in the gut is involved. Thus, invasion and fimbrial genes required for colonisation have been identified (Clayton et al., 2008, Morgan et al., 2004) suggesting physical contact was required. An alternative approach would be to analyse the patterns of gene expression by microarray analysis at the site of colonisation (caeca). This has been done for a number of niches and is now being applied to intra-cellular infection but has not so far been applied to the intestine. The S. Enteritidis transcriptome during the colonisation of the caeca of one day chicks was characterised by Agilent microarray. The microarray results were evaluated by real-time PCR with 96% compatibility. The pattern of gene transcription was different in the intestine compared with broth culture. Thirty four percent of the genes showed a significant change in level of expression. Major changes occured from adaptation to the caecal environment with up-regulation of genes required for energy generation and carbohydrate metabolism/transport, while amino acids and nucleotide metabolism, translation, replication and cell wall biogenesis genes were among the down-regulated genes. Fumarate respiratory and osmotic response genes were selected from the up-regulated genes and were mutated and tested in the lab for their inhibitory effect and for competitive growth under anaerobic and osmotic environments showing variable responses. Association between chicken colonisation phenotype and gene mutation indicated that genes associated with osmolarity was more important than tri carboxylic acid (TCA)-associated genes in their contribution to the colonisation phenotype. There is considerable scope for improvement in inactivated vaccines through a more rational approach. An inactivated vaccine prepared by formalising S. Enteritidis harvested directly from the chicken caeca was thought to be more protective than bacteria grown in vitro. Unfortunately this was not the case. Expected reasons for this failure are explained, and alternative approach to producing a proper effective inactivated vaccine is suggested.